Complex Brush‐Like Macromolecular Architectures via Anionic and Ring Opening Metathesis Polymerization: Synthesis, Characterization, and Thermal Properties. Issue 1 (27th September 2017) - Theodosopoulos, George V.; Bitsi, Spyridoula‐Lida; Pitsikalis, Marinos
Abstract: Combination of anionic and ring opening metathesis (ROMP) polymerizations is conducted for the synthesis of different series of brush polymers adopting the macromonomer methodology. Specifically, poly( tert ‐butoxystyrene) (P t BOS), polystyrene (PS), and poly(ethylene oxide) (PEO) macromonomers, having end norbornene groups, are prepared by anionic polymerization techniques and suitable termination reactions or functional anionic initiators. These macromonomers are either homopolymerized or copolymerized by ROMP employing Ruthenium Grubbs catalysts of the 1st or 3rd generation leading to the formation of polymer brushes. Using this synthetic approach, P t BOS polymacromonomers, P t BOS‐PEO block and random copolymacromonomers, and P t BOS‐PS random copolymacromonomers are prepared. Acidic hydrolysis of the tert ‐butoxy groups of the P t BOS brushes affords the corresponding polyhydroxystyrene (PSOH) brushes. Subsequent activation of the hydroxyl groups upon reaction with triphenylmethyl potassium and addition of ethylene oxide lead to the formation of PEO brushes on the PSOH brushes (brush on brush structures). These materials are thoroughly characterized by size exclusion chromatography, and 1 H‐NMR spectroscopy. The thermal properties are studied by differential scanning calorimetry, thermogravimetric analysis, and differential thermogravimetry. Abstract : Anionic and ring‐opening metathesis polymerizations are employed for the synthesis of novel brush‐like structures based on a polynorbornene backbone and poly( tert ‐butoxystyrene), polyhydroxystyrene, polystyrene, and poly(ethylene oxide) side chains.